Revenue Cost Ratio and Value-Added Household Industry Robusta Powder Coffee Company - Letty Fudjaja; Ni Made Viantika; Muhammad Ridwan; Andi Rifdah Rosyadah Saad; Mahyuddin Riwu (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2023)
Coffee is one of the promising agricultural commodities. Sound processing and advanced processing will provide added value and increase income. CV. Berkat Asia is a household-scale ground coffee industry located in Sinjai Borong District. They process robusta coffee from local farmers to packaged ground coffee. This study aims to analyze the added value of income in CV. Berkat Asia. This research was conducted in January 2022 by applying case study research. The data were then analyzed using income and value-added analysis using the Hayami method. The results showed that the daily income for processing ground coffee was IDR. 10.3 million . The annual income is IDR. 2.4 billion. The added value generated is IDR. 12 thousand/kg with a value-added ratio of 30.23%. The industrial value added is classified as a medium ratio because the added value is above 15%, with daily and annual R/C ratios of 1.34 and 1.32, respectively.